1990
DOI: 10.1038/jcbfm.1990.40
|View full text |Cite
|
Sign up to set email alerts
|

Ornithine Decarboxylase Activity and Putrescine Levels in Reversible Cerebral Ischemia of Mongolian Gerbils: Effect of Barbiturate

Abstract: Summary: Reversible cerebral ischemia was produced in anesthetized Mongolian gerbils by occluding both com mon carotid arteries. After 5 min of ischemia, brains were recirculated for 8 or 24 h. Treated animals received a single intraperitoneal injection of pentobarbitol (50 mg/ kg) immediately after the anuerysm clips were removed. At the end of the experiments, animals were reanesthe tized and their brains frozen in situ. Tissue samples were taken from the cerebral cortex, lateral striatum, CAl sub field of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…In the gerbil brain following 20 min of cerebral ischemia (bilateral common carotid artery occlusion) ODC activity was increased about 7-fold after 4 h of recirculation (Dempsey et al, 1988). A similar rise in enzyme activity was found in the brain of gerbils after only 5 min of ischemia (bilateral common carotid artery occlusion) and 8 h of recirculation (Paschen et al, 1990a): A sharp increase (up to 15-fold) was observed in the cerebral cortex, striatum, and hippocampal CAl-subfield and thalamus, but activity did not change significantly in the cerebellum, a region in which blood flow is not critically reduced in this animal model during vascular occlusion. In a recent paper, Koenig and coworkers (1990) illustrated that in transient cerebral ischemia of the gerbil ODC activity was significantly increased at three different time points: during the first 2 min of vascular occlusion (increase to about 150%), within the first 15 min of recirculation following 15 min of ischemia (to about 300%), and again after 6 h of recirculation.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…In the gerbil brain following 20 min of cerebral ischemia (bilateral common carotid artery occlusion) ODC activity was increased about 7-fold after 4 h of recirculation (Dempsey et al, 1988). A similar rise in enzyme activity was found in the brain of gerbils after only 5 min of ischemia (bilateral common carotid artery occlusion) and 8 h of recirculation (Paschen et al, 1990a): A sharp increase (up to 15-fold) was observed in the cerebral cortex, striatum, and hippocampal CAl-subfield and thalamus, but activity did not change significantly in the cerebellum, a region in which blood flow is not critically reduced in this animal model during vascular occlusion. In a recent paper, Koenig and coworkers (1990) illustrated that in transient cerebral ischemia of the gerbil ODC activity was significantly increased at three different time points: during the first 2 min of vascular occlusion (increase to about 150%), within the first 15 min of recirculation following 15 min of ischemia (to about 300%), and again after 6 h of recirculation.…”
supporting
confidence: 54%
“…Barbiturates that have been shown to be neuroprotective in transient cerebral ischemia (Hallmayer et al, 1985;Kirino et al, 1986) suppressed the postischemic activation of ODC gene expression completely (Dempsey et al, 1991) but, notably, had no significant effect on postischemic changes in ODC activity (Paschen et al, 1990a). An opposite dissociation between ODC transcription and enzyme activity was observed after treating animals with the N-methyl-D-aspartate (NMDA) receptor antagonist MK-801.…”
mentioning
confidence: 88%
“…The assessment of these effects of PA sheds some light on their role as mediators of pathological processes, at least in the early post-traumatic period. 8 Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 7/6/15 5:06 PM…”
Section: Discussionmentioning
confidence: 99%
“…This increase in extracellular EAA levels is also very sen sitive to temperature and contributes to the deleterious intracellular accumulation of Ca2*. An additional factor of N-methyl-D-aspartate (NMDA) deregulation may be the enhanced metabolism of polyamines that occurs dur ing ischemia, together with an increase in ornithine de carboxylase activity and putrescine formation [20].…”
Section: Excitatory Amino Acids (Eaa)mentioning
confidence: 99%